(untitled) (Research, Society and Development, 2020)
This paper discusses some limitations and possibilities that may contribute to a more sustainable use in water resources management from the managers’ perception of a multinational company of the automotive industry inserted in Paulista Macrometropolis. We present part of the first findings during the prospecting period in the industry, in 2016, that impact the decision making in the industry water management and bring a reflection on these actions. The research methodology is qualitative, recorded interviews were conducted with managers responsible for water resources on water management from 2000 to 2015, when the industry reduced its water consumption by 50%. Also, we performed participant observation on the shop floor. Information analysis was based on the content analysis method. The initial considerations indicate an organizational culture in which the decision-making of the actors prioritize the economic aspects over the social and environmental ones in the Sustainability tripod. The reports are part of the results of ongoing doctoral level research.